KONTRIBUSI TEORI DAN TEKNOLOGI KOMUNIKASI DALAM TEKNOLOGI PEMBELAJARAN - Bambang Warsita (Balai Besar Guru Penggerak Jawa Timur, 2014)
Every technology is built on the basis of certain theory, instructional technology is built on the basis of principles that is drawn from communication theory and results of research in the utilization of communication technology. This study aims to gain an overview of the contribution of communication theory and technology in instructional technology. Instructional technology is built based on the principles that is drawn from various theories, one of them is a theory of communication. Instructional technology is utilizing communication media based on communication technology (broadcasting technology) which is a radio and television. The results of this study indicates that contribution or support theory and communication technology in the presence of various Instructional technologies as an alternative learning model in which innovative based communications technology to solve problems of learning and teaching. For instance, the use of books, films, radio broadcasts, television broadcasts, etc. in efforts to use communication technologies to support the quality improvement of learning process. AbstrakSetiap teknologi dibangun atas dasar suatu teori tertentu, teknologi pembelajaran dibangun atas dasar prinsip-prinsip yang ditarik dari teori komunikasi dan hasil hasil penelitian dalam pemanfaatan teknologi komunikasi. Kajian ini bertujuan untuk memperoleh gambaran tentang kontribusi teori dan teknologi komunikasi dalam teknologi pembelajaran. Teknologi pembelajan dibangun berdasarkan pada prinsip-prinsip yang ditarik dari berbagai teori, salah satunya adalah teori komunikasi. Teknologi pembelajaran memanfaatkan media komunikasi yang berbasis teknologi komunikasi (teknologi broadcasting) yaitu radio dan televisi. Hasil kajian ini menunjukkan bahwa kontribusi atau dukungan teori dan teknologi komunikasi dalam teknologi pembelajan yaitu adanya berbagai model pembelajaran alternatif yang inovatif berbasis teknologi komunikasi untuk memecahkan masalah belajar dan pembelajaran. Misalnya penggunaan buku, film, siaran radio, siaran TV, dan lain-lain dalam upaya pemanfaatan teknologi komunikasi untuk menunjang peningkatan kualitas proses pembelajaran.